Asuhan Keperawatan pada Ny. T Keluarga Tn. H dengan Gangguan Sistem Kardiovaskuler : Hipertensi di Desa Purwodadi RT 02 RW 01 Kecamatan Tonjong Kabupaten Brebes - Hanum Alya Saputri; Tati Karyawati; Arisnawati Arisnawati (STIKes Ibnu Sina Ajibarang, 2025)
Non-communicable diseases (NCDs) are a major challenge in today's health development. One category of these diseases is hypertension, which is classified as a chronic disease with a relatively high mortality rate. Hypertension serves as a major predictor for various chronic diseases and is a common disease found in the community (Putri et al., 2025). If not managed properly, hypertension can lead to more serious complications such as stroke, coronary heart disease, diabetes, kidney failure, and blindness. Stroke (51%) and coronary heart disease (45%) are the leading causes of death related to hypertension (Pokhrel, 2024). The increasing prevalence of hypertension along with changes in lifestyle and unhealthy eating patterns adds to the global health burden. Therefore, effective management of hypertension is essential to prevent further complications. Appropriate hypertension management and regular monitoring can reduce the risk of related diseases, improve quality of life, and reduce mortality caused by complications of heart disease and stroke. Preventive and promotive efforts through health education are key to reducing the prevalence of hypertension in the community.